Emerging economies' supply shocks and Japan's price deflation: International transmissions in a three-country DSGE model - Naohisa Hirakata; Yuto Iwasaki; Masahiro Kawai (Asian Development Bank Institute (ADBI), 2014)
This paper examines the international transmission effects that a positive supply shock in emerging economies may have on inflation in developed economies. We construct a dynamic stochastic general equilibrium (DSGE) model for three countries and analyze the impact of a supply shock in an emerging economy, the People's Republic of China (PRC), on inflation rates in two developed economies, the United States (US) and Japan. We demonstrate that the assumed asymmetric trade structures among the three countries and the PRC&'s choice of exchange rate regime influence the international transmission of a supply shock in the PRC. Specifically, Japan is under a greater deflationary pressure than the US because of its vertical trade specialization vis-à-vis the PRC and the PRC's USdollar- pegged regime. This outcome suggests that, even though Japan and the US may face common positive supply shocks from emerging economies, the deflationary impact of the shock is greater for Japan.
Keywords: F32; F41; F44; F47; 330; supply shocks; emerging economies; trade structure; exchange rate regimes; three-country DSGE model; Angebot; Schock; Inflationsrate; Dynamisches Gleichgewicht; China; USA; Japan